Effects of acute microplastic exposure on physiological parameters in Tubastrea aurea corals. (April 2021) - Liao, Baolin; Wang, Junjie; Xiao, Baohua; Yang, Xiaodong; Xie, Ziqiang; Li, Dongdong; Li, Chengyong
Abstract: Pollution of marine environments with microplastic particles has increased rapidly during the last few decades and its impact on marine lives have recently gained attention in both public and scientific community. Scleractinian corals are the foundation species of coral reef ecosystems that are greatly affected by the microplastics (MPs), yet little is known about the effects of microplastics on the coral azooxanthellate. In the present study, effects of the exposure and ingestion of polyvinyl chloride (PVC), polyethylene (PE), polyethylene terephthalate (PET), and polyamide 66 (PA66) were studied on the physiological responses of Tubastrea aurea . Our results shows that coral ingested microplastics in four treatment groups and the exposure of microplastics inhibited the antioxidant capacity, immune system, calcification and energy metabolism of the coral Tubastrea aurea . Superoxide dismutase (SOD), catalase (CAT), alkaline phosphatase (AKP), and total antioxidant capacity (TAC) were reduced by 29.4%, 35.5%, 73.9%, and 52.2% in the corals exposed to PVC, respectively. PET microplastics impacted more severely on pyruvate kinase (PK), Na, K-ATPase (Na, K-ATP), Ca-ATPase (Ca-ATP), Mg-ATPase (Mg-ATP), Ca-Mg-ATPase (Ca, Mg-ATP), and glutathione (GSH). Activity of these enzymes decreases to 89.6%, 66.7%, 63.6%, 60.4%, 48.4%, and 50.5% respectively. We anticipate that this work will provide important preliminary data for better understanding the effects of MPs on stony corals azooxanthellate. Graphical abstract: Unlabelled Image Highlights: The effects of microplastics were investigated in Tubastrea aurea coral. Exposure to microplastics repressed the antioxidant capacity and immune system. Exposure to microplastics inhibited energy metabolism. Exposure to microplastics repressed calcification process.